2013
DOI: 10.3727/096368912x655208
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Induced Pluripotent Stem Cell Technology as a Potential Clinical Therapy for Spinal Cord Injury

Abstract: Transplantation therapies aimed at repairing neurodegenerative and neuropathological conditions of the central nervous system (CNS) have utilized and tested a variety of cell candidates, each with its own unique set of advantages and disadvantages. The use and popularity of each cell type is guided by a number of factors including the nature of the experimental model, neuroprotection capacity, the ability to promote plasticity and guided axonal growth, and the cells' myelination capability. The promise of stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 426 publications
(533 reference statements)
0
43
1
1
Order By: Relevance
“…6 By immunohistochemical staining analysis, the protein levels of BDNF and VEGF were significantly higher in Ngn2-ADSCs group and ADSCs group compared to those in control group (a, b, *P \ 0.05); and the protein levels in Ngn2-ADSCs group were significantly higher than those in ADSCs group (a, b, # P \ 0.05) Cell Mol Neurobiol Astrocyte proliferation is a major contributor to glial scar formation after SCI (White and Jakeman 2008). Scar tissue is now widely accepted to be both a physical as well as a chemical barrier for axonal growth and regeneration, at least in experimental SCI (Kramer et al 2013). Our study indicated that GFAP expression at the injury site in the Ngn2-ADSCs group was decreased compared with that in the other two groups on day 14 after transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…6 By immunohistochemical staining analysis, the protein levels of BDNF and VEGF were significantly higher in Ngn2-ADSCs group and ADSCs group compared to those in control group (a, b, *P \ 0.05); and the protein levels in Ngn2-ADSCs group were significantly higher than those in ADSCs group (a, b, # P \ 0.05) Cell Mol Neurobiol Astrocyte proliferation is a major contributor to glial scar formation after SCI (White and Jakeman 2008). Scar tissue is now widely accepted to be both a physical as well as a chemical barrier for axonal growth and regeneration, at least in experimental SCI (Kramer et al 2013). Our study indicated that GFAP expression at the injury site in the Ngn2-ADSCs group was decreased compared with that in the other two groups on day 14 after transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…Researchers would then be able to simulate the conditions caused by aberrant genes of patient-specific iPSCs in a dish or in a tube. On the other hand, the expense incurred by the generation of certain genetic mutations in cell lines or animal models can be an economical roadblock to large-scale drug development and disease modeling [2,63]. From this point of view, the generation of patient-specific iPSCs often costs less than the generation of animal disease models or genetically engineered animals.…”
Section: Part 2 Clinical Applications Of Ipscsmentioning
confidence: 99%
“…The development of cell-based therapies aimed at repairing neuropathological and neurodegenerative conditions of the CNS have been utilized and tested a variety of cell candidates, each with its own unique set of advantages and disadvantages [6]. The use and popularity of each cell type are guided by a number of factors including neuroprotection capacity, the ability to promote plasticity and guided axonal growth, and the cell myelination capability [6].…”
Section: Introductionmentioning
confidence: 99%
“…The development of cell-based therapies aimed at repairing neuropathological and neurodegenerative conditions of the CNS have been utilized and tested a variety of cell candidates, each with its own unique set of advantages and disadvantages [6]. The use and popularity of each cell type are guided by a number of factors including neuroprotection capacity, the ability to promote plasticity and guided axonal growth, and the cell myelination capability [6]. Various stem cells, such as multipotent adult progenitor, mesenchymal, haemopoietic, umbilical cord blood (UCB), and embryonic stem cells (ESCs), have the potency to differentiate into the neural cells [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%